(untitled) (Research, Society and Development, 2021)
Objective: Analyze the effectiveness of art therapy as a complementary treatment to the pharmacological for elderly people with depression, also present the disease symptons and the way it manifests itself in this portion of the population. Methodology: It is an integrative review of an exploratory nature and a qualitative approach, where secondary sources of research were used to collect bibliographic data. The bibliographic search was carried out in the Lilacs, PubMed and Virtual Health Library databases with a 5-year period (2016-2021). Results: Two studies of the clinical trial and observational study type were analyzed, in which the elderly were selected to be part of a control group and an experimental group, where they underwent tests that measured the level of depression, anxiety and self-esteem, at the beginning of the study and at the end of the application of art therapy sessions. Conclusion: Despite the limitations and scarcity of studies related to the theme, it is evident that art therapy has proved to be a great form of treatment complementary to depression, since with the sessions the elderly participants were able to establish interpersonal relationships, combating one of the most evident symptoms of depression disease, which is social isolation, in addition to showing a significant improvement in the symptoms of depression, anxiety and self-esteem in relation to the control group. In this context, it is important that further studies are carried out so that the practice is more widespread, since currently art therapy is too underused.